Promoting Regional Power Trade : The Southern African Power Pool - O'Leary, Donal T.; Charpentier, Jean-Pierre; Minogue, Diane (World Bank, Washington, DC, 2012)
The Southern African Power Pool (SAPP), the first formal international pool to be set outside North American and Western Europe, was inaugurated in 1995. While the utilities of southern Africa have been importing and exporting electricity for four decades, these trades occurred through bilateral contracts that were complex and often difficult to administer. The objective of shifting to the pool is to create a more efficient regional market. Although physically the pool is still embryonic and trade volumes average roughly 3 percent of production, confidence in the market and mutual trust between the members are being strengthened and sector coordination is dramatically improved. This Note reviews the factors that have eased the way for the pool agreements and the challenges that remain in getting the multilateral trading operation under way.